2022
DOI: 10.1093/jscr/rjac015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on delayed presentations of necrotising fasciitis

Abstract: The purpose of this study was to determine the impact of coronavirus disease 2019 (COVID-19) on the delayed presentation of necrotising fasciitis (NF). A retrospective study was conducted of adult patients (≥16 years old) diagnosed with NF at a hospital from 2017 to 2020. A quantitative comparative analysis for the COVID-19 group and control group between 2017 and 2019. Structured interviews were conducted to examine the impact of COVID-19 on patients. There were 6 patients in the COVID-19 group and 10 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…This can be linked to the transformation of less urgent complaints into more serious conditions due to delayed presentation corroborated by multiple case reports. [17] [18] [19] Our previous studies have demonstrated instances of severe disease with delays in presenta-tions for pathologies such as necrotising fasciitis [20], due to fears of contracting COVID-19 at hospitals and/or clinics. This study provided insight into the mindset of the SWSLHD population at the time where all patients denied any reason for delay to ED with sound knowledge of personal protection and sufficient access to COVID-19 information.…”
Section: Discussionmentioning
confidence: 99%
“…This can be linked to the transformation of less urgent complaints into more serious conditions due to delayed presentation corroborated by multiple case reports. [17] [18] [19] Our previous studies have demonstrated instances of severe disease with delays in presenta-tions for pathologies such as necrotising fasciitis [20], due to fears of contracting COVID-19 at hospitals and/or clinics. This study provided insight into the mindset of the SWSLHD population at the time where all patients denied any reason for delay to ED with sound knowledge of personal protection and sufficient access to COVID-19 information.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, NF is associated with significant mortality and this is further increased when caused by atypical organisms such as S. marcescens [ 2 ]. A recent study by Nguyen et al showed that in Australia, patients with NF during the COVID-19 lockdown tended to present later and more critically ill, leading to a 50% mortality rate compared to 0% in their pre-COVID-19 cohort [ 8 ]. Of note, none of the patients in the study actually tested positive for COVID-19 (they were distinguished by study period only, i.e., pre- and during COVID-19).…”
Section: Discussionmentioning
confidence: 99%
“…While studies such as that by Nguyen et al suggest that the mortality rate of NF during COVID-19 was higher, this is likely due to further progression of pathology due to delayed presentation (mean of 4.1 days) as demonstrated by more highly deranged biochemical results (i.e., doubling of creatinine and lactate, and tripling of urea) [ 8 ]. In turn, the LRINEC score in these patients was an average of 5.9, which equates to an intermediate (50-75%) risk of developing NF.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work identified that those with necrotising fasciitis in the COVID-19 group had a significantly longer mean onset of symptoms till hospital presentation of 4.1 days, longer mean operative time, more likely to be admitted to ICU and not survive compared to their counterparts. 15 A Melbourne based study who experienced different restrictions compared to Sydney reported those who had operations after-hours in the COVID-19 period were more likely to present with severe cholecystitis. 16 An Israeli study who had similar experiences with lockdowns, but at the time overall better vaccination rates compared to Australia reported significant delays of presentation from onset of symptoms resulting in worse biochemical and clinical parameters compared to the control cohort.…”
Section: Discussionmentioning
confidence: 99%